A shape memory scaffold for body temperature self‐repairing wearable perovskite solar cells with efficiency exceeding 21%. Issue 12 (23rd August 2022) - Xue, Tangyue; Huang, Zengqi; Zhang, Pei; Su, Meng; Hu, Xiaotian; Wu, Tingqing; Fan, Baojin; Chen, Gangshu; Yu, Guanghui; Liu, Wentao; Liu, Xuying; Zhang, Yiqiang; et al.
Abstract: Grain boundary cracks in flexible perovskite films can be repaired by filling with self‐repairing polymers during the preparation and wearable operation. However, the self‐repairing polymers are commonly active through external heating or humidification treatments, which cannot match with the human body's temperature tolerance of wearable devices. Herein, a body temperature‐responsive shape memory polyurethane (SMPU) is demonstrated to achieve the real‐time mechanical self‐repairing of grain boundary cracks (~37°C). Furthermore, the strong intermolecular interaction between SMPU and the uncoordinated Pb 2+ and I −, can reduce the trap density in perovskite films. The blade‐coated device achieves a power conversion efficiency (PCE) of 21.33%, which is among the best reported flexible perovskite solar cells (PSCs; 0.10 cm 2 ). Importantly, the device with SMPU can recover more than 80% of the PCE after 6000 cycles (bending radius: 8 mm). Finally, the flexible PSCs are used for wearable solar power supply of a smartphone, which show great potential for self‐repairing wearable electronics. Abstract : A body temperature‐responsive shape memory polyurethane (SMPU), with the strong hydrogen bonding force and shape memory effect, is demonstrated to achieve the self‐repairing of grain boundaries cracks (~37°C, recover 91% of the power conversion efficiency [PCE]). Accordingly, the blade‐coated flexible perovskite solar cell (PSC) with SMPU achieves a record PCE of 21.33% and can be used as the power supply for a smartphone.